Kaolinitic calcined clays - Portland cement system: Hydration and properties - Tironi, Alejandra (2014)
This paper examines the influence of type of kaolinite in the raw clay on the performance of calcined clays as supplementary cementing materials. Two kaolinitic clays were characterized, calcined then ground and used as partial replacement of Portland cement at 15% and 30% by mass. The results show that both kaolinitic calcined clays are an effective pozzolan with different reaction rate. The reactivity is related to the specific surface area obtained after calcination and it depends on the structure of kaolinite. Raw clay containing disordered structure presents a very high pozzolanic activity allowing high replacement levels (30%) in blended cements.